Determination of Trace Amount of Cadmium by Atomic Absorption Spectrometry in Table Salt after Solid Phase Preconcentration Using Octadecyl Silica Membrane Disk Modified by a New Derivative of Pyridine - Mahmood Payehghadr; Sousan Esmaeilpour; Mohammad Kazem Rofouei; Laleh Adlnasab (Journal of Chemistry)
Silica-C18 bonded disk modified by a four-dentate Schiff base has been used for preconcentration of cadmium in table salt samples followed by flame atomic absorption spectrometry. The method is based on the adsorption of Cd on 1,2-bis(pyridin-2-ylmethylene) hydrazine as Schiff base ligand on silica-C18 disk. The effects of several factors such as type and concentration of the eluent, pH of sample solution, amount of ligand, and breakthrough volume have been optimized based on one variable at a time. In optimum conditions (type of eluent, HNO3 1.0 mol/L; volume of eluent, 5.0 mL; solution pH, 9.0; breakthrough volume, 1000.0 mL), preconcentration factor of the present method is about 200. The resultant limit of detection is 5.0 μg/L. Finally, the performance of the method has been evaluated for extraction and determination of Cd (II) in salt samples at milligram per liter concentration, and satisfactory results have been obtained (RSD ≤ 2.0%).